Construction of a Luminescent Cadmium-Based Metal–Organic Framework for Highly Selective Discrimination of Ferric Ions - Li-Li Xu (MDPI AG, 2021)
Fluorescent metal–organic frameworks (MOFs) are ideal materials for sensors because of their adjustable pore size and functional groups, which provide them with favorable metal ion selective recognition. In this paper, a new cadmium-based MOF was synthesized using Cd(NO3)2·4H2O and 3,3′,5,5′-biphenyltetracarboxylic acid by solvothermal method. CdBPTC owned three types of channels with dimensions of approximately 8.4 × 8.3 Å, 6.0 × 5.2 Å, 9.7 × 8.4 Å along a, b, and c axis, respectively. This MOF has high selectivity to ferric ions and shows excellent anti-inference ability toward many other cations. The results indicate that the fluorescence quenching efficiency of CdBPTC is close to 100% when the concentration of Fe3+ reaches 1.0 × 10−3 mol·L−1. Moreover, the luminescent intensity at 427 nm presents a linear relationship at a concentration range of 2.0 × 10−4~7.0 × 10−4 mol·L−1, which can be quantitatively expressed by the linear Stern–Volmer equation I0/I = 8489 [Fe3+] − 0.1400, which is comparable to the previously reported better-performing materials. Competitive energy absorption and ion exchange may be responsible for the variation in fluorescence intensity of CdBPTC in different Fe3+ concentrations.